Classification of cleft lip and palate: An Indian perspective - Karoon Agrawal (Wolters Kluwer Medknow Publications, 2014)
Classification of the cleft has evolved over a century. Many descriptive, diagrammatic, and coding systems have been proposed to be used. However, there are only few which have stood the test of time. One of them is Indian classification. Indian classification of cleft lip (CL) and palate proposed in 1975 is a popular classification in India presently. There are numerous combinations of cleft deformities, and we found that some of them could not be classified appropriately with the original classification. The clefts are classified in three groups: CL as Group 1, cleft palate as Group 2 and Group 3 for combined CL, alveolus and palate in continuity. Originally right, left, midline, and alveolus were abbreviated. To make the classification wholesome, the original classification has been revisited and presented with additional features. The basic classification in three groups remains as original. Additional abbreviations have been added to classify the special situations. Partial, submucosal, Simonart's band, protruding premaxilla, and microform have been added to the list of abbreviations. This classification has been used for over 30 years by the author in over 4000 cleft patients. We find it simple to use, versatile enough to classify almost all possible cleft combinations, easy for communication during discussion and convenient to write as diagnosis in patients' files. Easy computer archiving and efficient retrieval of the data are the special features of this classification.